Thermal study of MHD hybrid nano fluids confined between two parallel sheets: Shape factors analysis - Bahram Jalili; Pooriya Majidi Zar; Dong Liu; Chen-Hui Ji; Payam Jalili; Mostafa A.H. Abdelmohimen; Davood Domiri Ganji (Case Studies in Thermal Engineering)
This article discusses the heat and air transfer characteristics of stable magnetohydrodynamic nanofluid flow between two interconnected sheets under the influence of a magnetic field. The nanofluid is a mixture of equal proportions of ethylene glycol and water. This study examined hybrid nanoparticles containing multi-walled carbon nanotubes (MWCNT) and silver (Ag). This research presents, for the first time, a new method for solving nonlinear equations using HPM Python and AGM Python. In addition, the symbolic solution to HPM and AGM has been attained by employing SymPy and SciPy libraries in Python. The results are presented graphically by comparing them with the fourth-order Runge-Kutta number. The final results reflect a high level of agreement between the analytical and numerical methods on the one hand and HPM Python and AGM Python on the other hand. This examination also investigates the effect of various parameters, including magnetic properties, viscosity coefficients, thermophoretic parameters, Brownian parameters, and nanofluid parameters such as velocity, temperature, and concentration. The results prove that velocity and concentration increase as the magnetic field decreases, whereas the temperature displays an opposite trend. As the Schmidt number increases, both the Nusselt number and concentration decrease. The relationship between concentration and temperature with respect to the Prandtl number indicates that when the Prandtl number decreases, the temperature increases while the concentration declines. It is important to note that the employment of hybrid nanofluids leads to an increase in velocity, temperature, and concentration.